Legal issues of land acquisition in Zanzibar - Hikmany, Abdul Nasser H; Syed Abdul Kader, Sharifah Zubaidah; Othman, Ahmad Azam (2016)

(untitled)
The Constitution of Zanzibar 1984, the Land Tenure Act 1992 and the Land Acquisition Decree 1909 introduces conflicting concepts of „acquisition‟ and „termination‟. As there is a law on acquisition and another for termination, the land acquisition officers are faced with difficulties in selecting the right approach, not to mention that the law on termination does not have provisions in guiding the termination process e.g. notice and inquiry. The land acquisition institutions also seems not to be taking orders from a single authority, rather than the whole government and the local government having command in acquiring land rights and interests. The practicalities of the land acquisition which are enlighten in this paper, have identified the use of force in acquiring private lands for private investment. Other issues include discrepancies in paying compensation, deficiencies in the inquiry and notice and lack of court‟s approval prior to acquiring private land rights. The authors use different approaches to reveal significant issues in the land acquisition process in Zanzibar. These methods include an analysis of case laws and legislative instruments. The interviews conducted with the land officers and deprived land holders early 2015 are also referred. This paper concludes with recommendations for the Zanzibar Government to consider, such as amendment of laws and backing up the land acquisition process with principles of transparency, accountability and public participation.